Molecular Imaging of CaO Nanowhiskers in Living Organs - Butt, A. R.; Butt, I. A.; Nazir, A.; Ikram, M.; Sadiq, S.; Rashid, K.; Shujah, T.; Ali, S. (The Nucleus, 2015)
Nanomaterials are potential ingredients in the diagnostics and drug delivery of various neurological disorders. Calcium oxide (CaO) nanowhiskers were utilized in rats for molecular imaging in liver, kidney and brain. X-ray diffraction (XRD) describes a cubic phase crystal structure of CaO ranges between ~ 4 - 11 nm. Thermo-gravimetric analysis (TGA) shows that these nanostructures are stable above 953K. Scanning Electron microscope (SEM) image depicts the agglomerated nanowhiskers formation while Energy Dispersive X-ray (EDX) also confirms the only presence of Ca and O. These nanostructures were enwrapped with polyvinyl alcohol (PVA) as a biological marker. Necrosis, hemorrhages and degenerations were seen histopathologically in kidney, liver and brain following three months of administration of CaO nanostructures in the degree of severity. Immunofluorescence contemplate likewise could not distinguish any neuro-inflammations.